Iron Deficiency During Pregnancy - Jabborova Munisxon Abdubanon qizi; Jabborova Munisxon Abdubanon qizi (Open Academia, 2023)
This article provides information about iron deficiency during pregnancy, republican medical institutions, maternity complexes, the special condition of the female body, and the health care system of the Republic of Uzbekistan in modern conditions
Keywords: obstetric; gynecological; perinatal; reproductive